COMPOSITION AND STRUCTURE OF HERBACEOUS FLORA AND VEGETATION OF THE LOWER DELTA OF OUÉMÉ IN SOUTHERN BENIN - ADJAKPA, Boco Jacques; YEDOMONHAN, HOUNNANKPON; AGBANI, Pierre; AKPO, Léonard Elie (My University, 2012)
The composition of the herbaceous vegetation of the Lower delta of Ouémé was assessed using phytoecological data records performed following the method of Braun-Blanquet from a systematic sampling transect. The observations were made in 10 m x 10 m plots. Herbaceous flora consisted of 257 species distributed in 179 genera and 60 families which most represented species were Leguminosae, Cyperaceae, Asteraceae and onvolvulaceae. The most frequent species were: omoea aquatica (39%), Echinochloa pyramidalis (34%), Leersia hexandra (27%), Justicia anselliana (25%) and Alternanthera sessilis (22%). The number of species was around 7 in aquatic vegetation and 174 in fields and fallows. The diversity index was 0.33 to 3.42 bits with a Pielou equitability from 0.28 to 0.96. Species with wide biogeographical distribution types were dominant (53% of the area).
Keywords: Flora; herbaceous vegetation; composition; Lower Delta of Ouémé; southern Benin